UTILIZING A P-BAND SCATTEROMETER TO ASSESS SOIL WATER SATURATION PERCENT OF A BARE SANDY SOIL - Blumberg D.G.; Ronen G.; Ben-Asher J.; Freilikher V.; Vulfson L.D.; Kotlyar A.L. (My University, 2006)
A scatterometer operating in P-band at 441 MHz was used to estimate soil water content. This letter describes encouraging results of experiments that were undertaken in Israel at Yotvata and Ashalim experimental farms. The soil water saturation percent of the entire wetting and drying cycles created through irrigation of sandy agricultural soils were retrieved using the scatterometer, which yielded good agreement with gravimetric measurements of soil water content demonstrating that P-band provides relatively unambiguous estimates of the soil water saturation percent. © 2005 Elsevier Ltd All rights reserved.
Keywords: P-BAND; RADAR; SCATTEROMETER; SOIL WATER-CONTENT; SOIL-POTENTIAL; TDR